Inflammation rapidly recruits mammalian GMP and MDP from bone marrow into regional lymphatics - Serrano-Lopez, Juana; Hegde, Shailaja; Kumar, Sachin; Serrano, Josefina; Fang, Jing; Wellendorf, Ashley M; Roche, Paul A; Rangel, Yamileth; Carrington, Leolene J; Geiger, Hartmut; Grimes, H Leighton; Luther, Sanjiv; et al. (eLife, 2021)
Innate immune cellular effectors are actively consumed during systemic inflammation, but the systemic traffic and the mechanisms that support their replenishment remain unknown. Here, we demonstrate that acute systemic inflammation induces the emergent activation of a previously unrecognized system of rapid migration of granulocyte-macrophage progenitors and committed macrophage-dendritic progenitors, but not other progenitors or stem cells, from bone marrow (BM) to regional lymphatic capillaries. The progenitor traffic to the systemic lymphatic circulation is mediated by Ccl19/Ccr7 and is NF-κB independent, Traf6/IκB-kinase/SNAP23 activation dependent, and is responsible for the secretion of pre-stored Ccl19 by a subpopulation of CD205+/CD172a+ conventional dendritic cells type 2 and upregulation of BM myeloid progenitor Ccr7 signaling. Mature myeloid Traf6 signaling is anti-inflammatory and necessary for lymph node myeloid cell development. This report unveils the existence and the mechanistic basis of a very early direct traffic of myeloid progenitors from BM to lymphatics during inflammation.
Keywords: endotoxemia; inflammation; myeloid progenitors; circulation; lymphatics; bone marrow